The Effect of Financial Literacy and Financial Socialization on Financial Management Behavior of Investors in Greater Bekasi - Muhamad Syahwildan; Nugraha Nugraha; Nono Supriatna; Toni Heryana (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Financial intelligence refers to an individual's ability to effectively manage and utilize financial resources, which is considered an important indicator of success in personal financial management. Proper financial management enables individuals to maximize the value of their financial resources and protect themselves from potential financial difficulties. This study aims to examine the effects of financial literacy and financial socialization on the financial management behavior of investors in the Greater Bekasi area following the COVID-19 pandemic. A quantitative research approach was employed, with data collected through questionnaires distributed to 100 investors residing in the Greater Bekasi area. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with SmartPLS software. The analysis involved the assessment of the measurement model (outer model) and the structural model (inner model) to evaluate the validity, reliability, and hypothesized relationships among variables. The results indicate that financial literacy has a positive and significant effect on financial management behavior (p-value = 0.000), suggesting that higher levels of financial knowledge contribute to better financial decision-making and management practices. Financial socialization also demonstrates a positive influence on financial management behavior; however, the effect is not statistically significant at the 5% significance level (p-value = 0.093). These findings highlight the important role of financial literacy in shaping investors’ financial management behavior in the post-pandemic period.